Study for the Influence of Mineral Admixtures on the Workability of Self-compacting Concrete - WANG Kunyun; HU Diyong; YANG Zhu (Renmin Zhujiang)
As the most important performance of self-compacting concrete (SCC),the workability has been studied extensively and deeply.In addition to high sand ratio and low water-cement ratio,mineral admixtures also have a great impact on the workability of SCC.In order to promote the use and development of SCC,after consulting a large number of domestic and foreign documents,this paper summarizes the use and research status of mineral admixtures in SCC in recent years,reviews the influence of different mineral admixtures on the workability of SCC,and specifies their mechanism.Generally speaking,common admixtures such as fly ash,slag,silica fume and limestone powder can improve part of the workability of SCC,and the main mechanism includes the “morphological effect”,“water reducing effect” and “volume effect” of these admixtures.However,there are few studies on the effects of mineral admixtures such as copper slag,waste glass slag,bagasse ash,pumice powder and lithium slag on the workability of SCC,so they are still in doubt,and need to be further studied.